Italia/Chile Collaboration for LARC - Storini, M.; Cordaro, E. G. (Societa italiana di fisica, 1997)
An Antarctic Laboratory for Cosmic Rays (LARC) has been opened on the King George Island (Fildes Bay - Ardley Cove) during January 1991. The cosmicray detector is a standard 6-NM-64 type. The present status of the LARC project and relevant scientific goals for Solar-Terrestrial Physics are briefly outlined.